Erosion Effect on Non-Darcy Hydraulic Characteristics of Limestone and Mudstone Mixture - Chong Li; Sifeng He (Geofluids)
In order to study the water inrush mechanism of faulted rock mass, a series of erosion seepage experiments were carried out to test the non-Darcy hydraulic properties of a limestone and mudstone mixture. The test results are employed to verify and modify a classic permeability prediction model. Based on the evolution of mass loss rate, the erosion process can be divided into four stages, i.e., particle rearrangement, severe erosion, mild erosion, and stable seepage. During the erosion, the sample height decreases gradually, the water pressure at outlet grows first and then keeps stable, and the porosity and permeability decrease slightly first, then grow gradually and finally keep stable. The hydraulic properties show a more significant variation in the sample within high mudstone particle contents. Through the comparison of test results and the predicted results by the classic Carman-Kozeny model, it is found that the accuracy of the model is greatly affected by lithology. Based on this investigation, a revised model is proposed which introduces a proportional coefficient related to the rock composition, so as to increase the predicted precision in variable rock composition. The forecast accuracy of the revised model is much higher than the classical one in permeability although it decreases with the increase of mudstone content.